2021
DOI: 10.1136/jech-2021-216876
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of compliance with COVID-19 preventive behaviours: a latent class analysis of 20 000 UK adults

Abstract: BackgroundGovernments have implemented a range of measures to tackle COVID-19, primarily focusing on changing citizens’ behaviours in order to lower the transmission of the virus. Few studies have looked at the patterns of compliance with different measures within individuals: whether people comply with all measures or selectively choose some but not others. Such research is important for designing interventions to increase compliance.MethodsWe used cross-sectional data from 20 947 UK adults in the COVID-19 So… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
61
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 32 publications
12
61
2
2
Order By: Relevance
“…Socio-demographic factors associated with uptake of lateral flow testing included being younger, living with a dependent child, lower socioeconomic grade and thinking that you have had COVID-19 before. Previous research has found these factors to be consistently associated with non-adherence to behaviours that prevent the spread of COVID-19 11 18 36. However, the association between increased lateral flow testing and lower age has also been found in other data, largely driven by those of working age being more likely to complete a test 8 22.…”
Section: Discussionmentioning
confidence: 91%
“…Socio-demographic factors associated with uptake of lateral flow testing included being younger, living with a dependent child, lower socioeconomic grade and thinking that you have had COVID-19 before. Previous research has found these factors to be consistently associated with non-adherence to behaviours that prevent the spread of COVID-19 11 18 36. However, the association between increased lateral flow testing and lower age has also been found in other data, largely driven by those of working age being more likely to complete a test 8 22.…”
Section: Discussionmentioning
confidence: 91%
“…These groups have consistently been found to have lower adherence to rules throughout the pandemic. (3,4,23) Lack of knowledge may be contributing to lower adherence. Congruent with this idea is our finding that knowledge of self-isolation rules was lower among people who disagreed that they had enough information about self-isolation.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other evidence on internal health locus of control and uptake of health behaviours, 20,21 but not with another study which found that internal locus of control was associated with decreased self-reported adherence to Government guidance on social mixing. 11 This study measured self-reported adherence, which necessarily depends on participants' knowledge of guidance; evidence suggests that knowledge is sub-optimal. 8,22 Increasing knowledge about SARS-CoV-2 transmission and emphasising that an individual's behaviour can affect the spread of the virus may encourage uptake of protective behaviours such as lower risk social mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that women, older people, those with chronic illnesses, people who perceived measures to be more effective, people who perceived COVID-19 to be a more severe illness, and those who thought that others were also adhering to measures were more likely to adopt physical distancing behaviours. [8][9][10][11] A study investigating close contacts during the pandemic found that people who reported more contacts were less likely to think that COVID-19 would be a serious illness for them, were more likely to agree that they were likely to catch COVID-19, and were more concerned that they might spread COVID-19 to others. 4 These studies investigated factors associated with individual dimensions of social mixing, for example the number of times people had met up with friends or family socially, whether they came into close contact with others, or selfreported adherence to Government guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation